2006
DOI: 10.1542/peds.2005-2000h
|View full text |Cite
|
Sign up to set email alerts
|

Using Billing Data to Describe Patterns in Asthma-Related Emergency Department Visits in Children

Abstract: OBJECTIVES. To describe the development and evaluation of a pilot emergency department (ED)-based asthma surveillance system for childhood asthma visits based on billing data and to illustrate how the data can be used to document trends and patterns in ED visits for asthma in children.METHODS. During 2001 and 2002, aggregate reports based on ED billing data from 3 hospitals in western Michigan were obtained from a single physician billing company. Data were tabulated and graphed to show trends in the monthly n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Silverman et al (2003), after conducting a 2-week review of ED patient charts and billing data in 11 New York City hospitals, reported 75% of asthma diagnoses listed in patient charts were also coded as asthma in the billing data. Reeves et al (2006) reported similarly high concordance between asthma diagnoses listed in pediatric ED patient charts and billing data. Because we implemented a case-crossover design, each case served as his or her own control and confounding by between-person differences and covariates that do not change within individuals during the study period (sex, race) was eliminated (Carracedo-Martínez et al 2010).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Silverman et al (2003), after conducting a 2-week review of ED patient charts and billing data in 11 New York City hospitals, reported 75% of asthma diagnoses listed in patient charts were also coded as asthma in the billing data. Reeves et al (2006) reported similarly high concordance between asthma diagnoses listed in pediatric ED patient charts and billing data. Because we implemented a case-crossover design, each case served as his or her own control and confounding by between-person differences and covariates that do not change within individuals during the study period (sex, race) was eliminated (Carracedo-Martínez et al 2010).…”
Section: Discussionmentioning
confidence: 73%
“…The ED billing data used in this study are likely to reflect valid diagnoses of asthma (Reeves et al 2006; Silverman et al 2003). Silverman et al (2003), after conducting a 2-week review of ED patient charts and billing data in 11 New York City hospitals, reported 75% of asthma diagnoses listed in patient charts were also coded as asthma in the billing data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dataset could be used to further investigate the effects of multiple encounters, health insurance, and seasonality on pediatric asthma. Asthma surveillance systems should also be expanded to include survey and environmental data to provide a more comprehensive picture of asthma (18,24,25). This study demonstrates how existing datasets can be integrated to enhance the surveillance of pediatric asthma and provide greater insight into the burden of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Although hospitalization and ED records are available, few states have integrated the two datasets (18). The integration of ED and hospitalization record improves the surveillance of asthma by de-duplicating the records and assigning multiple records to unique individuals to accurately calculate rates (19).…”
Section: Introductionmentioning
confidence: 99%